Evaluation and management of oral complications in oral cancer patients undergoing radiotherapy - Amrita Aggarwal; Satyapal Yadav; Anshuman S Jamdade; Neeraj K Yadav; Shashank Gupta; Vishnu Sain (Wolters Kluwer Medknow Publications, 2023)
Background: Mucositis, xerostomia, dysgeusia, trismus, radiation caries, osteomyelitis, and osteoradionecrosis are a few examples of radiotherapy (RT) complications, eventually distressing the patient's life. Objectives: To study the oral complications emerging due to RT and evaluate dental management of such complications before, during, and post-RT in oral cancer patients. Methods: Patients were evaluated on various parameters, which include the Oral Hygiene Index Simplified (OHI-S), Periodontal Index (PI), Gingival Index (GI), D - Decayed, M - Missing due to caries, F - Filled, T - permanent teeth (DMFT) Index, mucositis, xerostomia, dysgeusia, and interincisal distance before, during (10th session and last session), and 1 month after the last session of RT were evaluated and compared. Statistical Analysis: The following tests were applied: Chi-square test, analysis of variance (ANOVA) test, and standard deviation method. Results: P value <0.001 in OHI-S, PI, GI, DMFT index, mucositis, xerostomia, and dysgeusia, which is statistically significant. There was no difference found statistically in the interincisal distance. Conclusions: Oral healthcare team serves a vital role in preventing and managing short- and long-term complications of RT. There should be a mandatory prerequisite to visit an oral physician before, during, and after RT for supportive and palliative oral care.